Propagación de luz en medios turbulentos - Pérez, Darío Gabriel (2002)
The study of phenomena occurring in a turbulent ﬂuid has been successively improved during the last 40 years. Speci cally, the concentration of a substance advected by the turbulence has received most of the attention, for it covers a wide range of natural and engineering settings: heat transport, dye di usion, microscopic organism movements, etc. These substances are described by scalar elds with a negligible back-e ect on the ﬂow; thus, they are called passive scalar elds. The turbulent refractive index also belongs to this class; this is not a novelty (?). The temperature is a passive scalar eld whenever it produces buoyancy forces smaller than the inertial stresses driving the ﬂow, and a direct calculation shows that its ﬂuctuations are proportional to those of the index. Our interest in lightwave propagation through turbulent media must start here then. That is, we have to comprehend the media before attempt a description of the propagation itself. In the forthcoming sections we will study the dynamics and stochastic properties of passive scalars, and eventually propose models for the refractive index.